Introduction to Glycobiology - Taylor, Maureen E Drickamer, Kurt (Oxford University Press, 2006)
"Introduction to Glycobiology describes the impact of the sugars on biological systems, explaining their functions at the molecular, cellular, and organismal level. With a new two-part structure, the book leads us through the essential principles and concepts upon which the discipline is grounded, before exploring the diverse roles of sugars throughout biological systems, including development, cell signalling, and protein trafficking. It also describes the importance of glycobiology in disease, and explains how an understanding of the link between the two is enabling us to develop new therapeutic strategies." "Taking the student from the fundamental principles to the frontiers of the subject, and with more learning features to help students to get the most from their studies, Introduction to Glycobiology remains the ideal resource for students and teachers alike."--Jacket.